FLIP-STIK FOR FLIPPED CLASSROOM: STATISTICS LEARNING E-MODULE ASSISTED BY FLIPBOOK TO PROMOTE STUDENTS' NUMERACY - Mayang Purbaningrum; Thoiffatul Khusnun Nisa'; Indri Rohmatul F. Febriani; Ahmad Wachidul Kohar (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
The existence of Covid-19 causes the need for learning innovations supporting online learning and numeracy to understand data. The integration of e-modules in flipbook on statistics material is expected to improve students' numeracy in online learning. This is a development study that aims to produce an e-module assisted by Flipbook which is valid and practical for learning statistics that has a potential effect on students' numeracy in a flipped classroom learning design.The e-module was developed through a formative evaluation stage involving 15 students of 8th grade junior high school. Data were collected and analyzed utilizing walkthroughs, questionnaires, interviews, and document review. Results indicate that the flipbook demonstrates the stages of flipped learning from out-of-class activities (independent learning experience at home, do assignments, and takes notes of less understandable) to in-class activities (deepening understanding of statistics through class discussions and working on problem-solving tasks). The flipbook developed meets the criteria of validity in terms of content and construct and ease of use. In addition, it has the potential effect to develop students' numeracy based on the document analysis of student responses regarding the process of formulating problems mathematically, employing formal mathematical structure, and interpreting solutions on a set of numeracy tasks.